Electrochemical immunosensor for detection of Mycobacterium tuberculosis - Mohd Azmi, Umi Zulaikha; Yusof, Nor Azah; Kusnin, Norzila; Md Noor, Siti Suraiya; Ong, Poh Shing; Ahmad Raston, Nurul Hanun (2018)
A rapid and sensitive sandwich electrochemical immunosensor was developed based on the fabrication of the graphene/polyaniline (GP/PANI) nanocomposite onto screen-printed gold electrode (SPGE) for detection of Mycobacterium tuberculosis (M. tuberculosis) antigen. The chemical bonding and morphology of GP/PANI-modified SPGE were studied by Raman spectroscopy and field enhance scanning electron microscopy-energy dispersive X-ray spectroscopy (FESEM-EDX), respectively. From both studies, it clearly showed that GP/PANI was successfully coated onto SPGE through drop cast technique. Cyclic voltammetry (CV) was used to study the electrochemical properties of the modified electrode. The effective surface area for GP/PANI-modified SPGE was enhanced when compared with bare SPGE. Differential pulse voltammetry (DPV) was used to detect the M. tuberculosis antigen. This proposed electrochemical immunosensor is sensitive, low sample volume, rapid, and disposable, which is suitable for tuberculosis detection in real samples.